2004
DOI: 10.1073/pnas.0402690101
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the attachment of a paramyxoviral polymerase to its template

Abstract: The nucleocapsid of measles virus is the template for viral RNA synthesis and is generated through packaging of the genomic RNA by the nucleocapsid protein (N). The viral polymerase associates with the nucleocapsid through a small, trihelical binding domain at the carboxyl terminus of the phosphoprotein (P). Translocation of the polymerase along the nucleocapsid during RNA synthesis is thought to involve the repeated attachment and release of the binding domain. We have investigated the interaction between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
239
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(260 citation statements)
references
References 43 publications
18
239
0
3
Order By: Relevance
“…analogy with the related MeV (44,74) and also based on ITC studies carried out in the presence of 1 M NaCl, which showed that the N TAIL -P XD interaction does not rely on polar contacts, we reasoned that the burying of apolar residues of N TAIL at the P XD surface could be the driving force in the P XD -induced folding of N TAIL . Indeed, although globular proteins contribute most of their hydrophobic residues to the protein core, IDPs expose their few hydrophobic residues to the surface, thereby allowing interaction with binding partners.…”
Section: Structural Models Of Henipavirus N Tail -P Xd Complexes and mentioning
confidence: 60%
See 3 more Smart Citations
“…analogy with the related MeV (44,74) and also based on ITC studies carried out in the presence of 1 M NaCl, which showed that the N TAIL -P XD interaction does not rely on polar contacts, we reasoned that the burying of apolar residues of N TAIL at the P XD surface could be the driving force in the P XD -induced folding of N TAIL . Indeed, although globular proteins contribute most of their hydrophobic residues to the protein core, IDPs expose their few hydrophobic residues to the surface, thereby allowing interaction with binding partners.…”
Section: Structural Models Of Henipavirus N Tail -P Xd Complexes and mentioning
confidence: 60%
“…The amino acid sequence of P XD and of the N TAIL region that was modeled in the complex is shown with the same color code. C, superimposition of the structural models (ribbon representation) of the P XD -N TAIL complexes of HeV (green) and NiV (orange) onto the crystal structure of a MeV chimeric construct (red) encompassing P XD (amino acids 459 -507 of P) and residues 486 -504 of N (PDB code 1T6O) (74). A multiple sequence alignment of Henipavirus and MeV P XD as obtained using ClustalW and ESPript is also shown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…a disorder-to-order transition upon binding to a partner) (41)(42)(43)(44). Several studies have confirmed the involvement of this ␣-MoRE in binding to XD, showing that the N TAIL region encompassing residues 486 -502 adopts an ␣-helical conformation when bound to XD (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)45). The ␣-MoRE is partly preconfigured in solution prior to XD binding (21, 24 -26), and binding to XD stabilizes the ␣-helical conformation, giving rise to a compact four-helix bundle in which the N TAIL -XD interface is stabilized by hydrophobic contacts (17,45).…”
Section: Measles Virus (Mev)mentioning
confidence: 90%